Robust optimization of a silicon lateral pin photodiode - Kalthom Tasirin S.; Susthitha Menon P.; Ahmad I.; Fazlili Abdullah S. (2023)
The objective of this paper is to optimize the process parameters for a Si lateral p-in photodiode to obtain high responsivity, frequency response, quantum efficiency and low transient time Four process parameters were chosen, namely the intrinsic region length, photo-absorption layer thickness, the incident optical power and the bias voltage. The Taguchi method technique was used to optimize the experiment. Two noise factors were used that consist of four measurements for each row of experiment in the L9array. ATHENA and ATLAS module from Silvaco Int. were used for fabrication simulation and electrical characterization. The results obtained for responsivity, quantum efficiency, frequency response and transient time after the optimization approach were 0.62A/W, 96.37%, 13.1 GHz and 2.516 x 10-11 respectively which correspond to the optimization value for intrinsic region length of 6 ?m, photo-absorption layer thickness of 50 ?m, incident optical power of 1 mW/cm2 and bias voltage of 3 V. As a conclusion, the optimum solution in achieving the desired high speed photodiode was successfully predicted by using Taguchi optimization method. The percent of improvement for quantum efficientcy is 25%.